Juan Filloy's Caterva and the geopolitics of the Joycean novel in Argentina. Issue 2 (1st February 2022) - Novillo-Corvalán, Patricia
ABSTRACT: James Joyce's Ulysses has had a profound impact on the Argentine literary imagination, renewing and redefining style, language, and narrative technique, as part of an expansive legacy that kicked off with Borges's early reception of Ulysses and translation of 'Penelope' in 1925 and gained increasing momentum throughout the twentieth century, peaking with the stylistic fireworks ignited by Cortázar's experimental novel Rayuela ( Hopscotch ) in 1963. Yet this impact, I suggest, raises not only stylistic but also ideological questions. In this essay, I engage with one of the most significant works of the Argentine Joycean tradition: Juan Filloy's modernist masterpiece Caterva (1937). In what follows, I insert Caterva within the long arc of Argentina's Joycean novelistic tradition in a reading that destabilises previous critical narratives from which it had been erased, while mapping out new transnational affiliations with Joyce. My claim is that Joyce's and Filloy's modernist novels intersect stylistically and ideologically through their use of rhetorical devices emulating the movement of trains and trams as quintessential symbols of modernity, but in a manner that foregrounds British imperialism as the engine powering infrastructure projects in Ireland and Argentina respectively within the intricate global networks of Empire.